The ineffectiveness of sanctions in crimes against honor in the judicial proceedings of the Tacna preparatory investigative court and its decriminalization in the Peruvian penal code, in the year 2009-2010. - Sarmiento Chambilla, Herminia (2013)
Objective: Specify the ineffectiveness of the sanctions described in Crimes against the Honor and if decriminalization of the Peruvian Penal code is required. Method: The work is for applied research, this level is given when the researcher examines a problem explains; also proposes legal solutions for the phenomenon to transform or improve for the sake of social justice. He's also a research partner - legal because they studied the facts and social relations regulated by legal norms and because it seeks to determine the ineffectiveness of the criminal penalties for offenses against the honor of the people. For this purpose we considered the information obtained through the application of the questionnaire, the documentary analysis, and the Certificate of Interview, as measuring instruments to study variables. Results: Of the files analyzed at least 27% of the files have been declared abandoned, 20% have reached judgment of acquittal, another 20% of the processes have been filed, 11% have been declared inadmissible, 10% have ended in dismissal, 6% have been declared inadmissible, 5% of cases have reached conviction, and 1% have been declared invalid. Conclusion: The 88% of legal professionals specialty in criminal sentences say they typified in honor crimes are ineffective and therefore it is necessary to decriminalize this type of crime Peruvian Penal Code.